Pengaruh Disiplin Kerja, Kompensasi dan Lingkungan Terhadap Kinerja Karyawan PT Dunia Aneka Usaha - Dwi Nur Khasanah; Yossinomita Yossinomita; Ayu Feranika (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Employee performance is a strategic aspect that plays an important role in achieving company goals, especially in facing increasingly fierce business competition. Employee performance is not formed directly, but is influenced by various internal organizational factors, such as work discipline, compensation systems, and work environment conditions. This study aims to analyze the influence of work discipline, compensation, and work environment on employee performance at PT Dunia Aneka Usaha. This study uses a descriptive quantitative approach. The sampling technique used is a saturated sample, so that the entire population of 70 employees was used as research respondents. Data were collected through questionnaires compiled based on indicators of each variable and measured using a Likert scale. Furthermore, the data were analyzed using validity and reliability tests to ensure the quality of the research instrument, as well as statistical analysis in the form of t-tests, F-tests, and multiple linear regression analysis to test the proposed hypotheses. The results of the study indicate that work discipline, compensation, and work environment have a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that improving work discipline, providing appropriate compensation, and creating a conducive work environment can encourage improved employee performance. Therefore, companies are advised to manage these three factors sustainably so that employee performance improves and organizational goals can be achieved optimally.